2001
DOI: 10.1086/318406
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Cosmic Web on Cluster Weak Lensing Mass Estimates

Abstract: In modern hierarchical theories of structure formation, rich clusters of galaxies form at the vertices of a weblike distribution of matter, with filaments emanating from them to large distances and with smaller objects forming and draining in along these filaments. The amount of mass contained in structure near the cluster can be comparable to the collapsed mass of the cluster itself. As the lensing kernel is quite broad along the line of sight around cluster lenses with typical redshifts near z=0.5, structure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
117
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 14 publications
1
117
2
Order By: Relevance
“…Then all the particles in the direct vicinity of these haloes are extracted and projected along a given direction. Hence, each extracted halo contains a cluster and its outer environment (Metzler et al 2001). The additional effect of the uncorrelated background and foreground matter distribution along the line of 2 http://www2.iap.fr/users/peirani/PLUS/plus.htm sight to distant gravitationally lensed galaxies will be treated as an additional Gaussian random field acting as a noise contribution (see e.g.…”
Section: Dark Matter Haloes In the Plus Cosmological Simulationmentioning
confidence: 99%
“…Then all the particles in the direct vicinity of these haloes are extracted and projected along a given direction. Hence, each extracted halo contains a cluster and its outer environment (Metzler et al 2001). The additional effect of the uncorrelated background and foreground matter distribution along the line of 2 http://www2.iap.fr/users/peirani/PLUS/plus.htm sight to distant gravitationally lensed galaxies will be treated as an additional Gaussian random field acting as a noise contribution (see e.g.…”
Section: Dark Matter Haloes In the Plus Cosmological Simulationmentioning
confidence: 99%
“…Figure 7 shows that almost the entire Planck cluster sample will be excellent targets for weaklensing surveys, having an extremely high S/N. Although line-of-sight projection can be a significant contaminant for weak-lensing studies of the general cluster population (Metzler, White, & Loken 2001;White, van Waerbeke, & Mackey 2002), it is less of a problem for the Planck sample, which consists primarily of the most massive systems. Our conclusions are thus in line with, although slightly stronger than, those of Bartelmann, who suggested that Planck clusters would form an excellent sample for weak-lensing followup.…”
Section: Follow-upmentioning
confidence: 99%
“…It is also limited to intermediate-redshift clusters for which the distant background galaxies are far enough behind the cluster. Gravitational lensing masses are also subject to systematics such as the determination of the redshift distribution of the sources or projection effects of matter structures near the cluster or along the line-of-sight (Metzler et al 2001;Hoekstra 2003;Meneghetti et al 2010).…”
Section: Introductionmentioning
confidence: 99%